Respon Pertumbuhan Tanaman Anggrek Bulan (Phalaenopsis amabilis) Terhadap Perlakuan Media Tanam dan POC Kulit Bawang Merah (Allium cepa) - Putri Rahmawati, Andhini; Karunia Binawati, Diah (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2024)
The Kalimas River is a river that crosses industrial, commercial, office and densely populated residential areas in the city of Surabaya. Various activities in the area will produce waste that has the potential to pollute the Kalimas River. The indicator of polluted waters is the abundance of coliform bacteria and faecal coliforms. In some cases, the coliform and faecal coliform bacteria have become resistant to antibiotics which are currently of global concern. This study was conducted to determine the level of contamination of coliform bacteria and faecal coliforms in the Kalimas River and the level of resistance to several antibiotics. This study uses observational quantitative methods with sampling using purposive sampling and grab sampling techniques. River water samples were taken from 3 location points, namely the Kalimas River which crosses Jasa Tirta I Karah, Taman Prestasi and PT. Kasa Husada. Determination of the number and density of coliform and faecal coliform bacteria was carried out using the MPN method and testing of bacterial resistance to antibiotics using the disc diffusion method. Antibiotics used were amoxicillin, tetracycline, chloramphenicol and ciprofloxacin. Data were analyzed using ANOVA level 5% test and LSD and Duncan follow-up test. The results showed that the total bacterial density in all samples from each location in the Kalimas River exceeded the predetermined water body quality standard criteria. The highest average number of coliform and faecal coliform bacteria was found at location P3, namely 1.6 x 105 MPN / 100 ml. These coliform and faecal coliform bacteria have a 100% resistance level to amoxicillin antibiotics and have 100% sensitivity to tetracycline, chloramphenicol, and ciprofloxacin antibiotics. Ciprofloxacin is an antibiotic that shows the highest sensitivity rates. Keywords: Kalimas River, pollution, coliform, faecal coliform , antibiotic resistance